METALDEHYDE TOXICITY: A BRIEF ON THREE DIFFERENT PERSPECTIVES - Saad, A.M.; Ismail, S.W.; Dahalan, F.A. (Journal of Civil Engineering, Science and Technology, 2017)
Extensive use of metaldehyde to combat agriculture pest creates environmental problems. Not limited to targeted pests, it also endangers non-target groups including the environment, humans and animals. Its solubility in water is capable of polluting drinking water sources and increases cost of water treatment. Despite the low level of concentration, metaldehyde is able to bioaccumulate over time and causes dysfunction in certain organs. Thus, this paper gives a brief view on the toxicity level of metaldehyde and the permissible concentration range of this compound for three different groups namely sediments and plants, water and animals.